La integración eléctrica en el Perú: Implicancias y retos - García Carthy, Fiorella (2020)
The concept of electrical integration refers to the process by which a group of countries decide to interconnect via electrical systems by means of an express agreement. The present article details the progress of said process and analyzes different international experiences, presenting the current panorama in Peru, offering interesting proposals and conclusions.